Genie in a blotter: A comparative study of LSD and LSD analogues' effects and user profile. (18th May 2017) - Coney, Leigh D.; Maier, Larissa J.; Ferris, Jason A.; Winstock, Adam R.; Barratt, Monica J.
Abstract: Objective: This study aimed to describe self‐reported patterns of use and effects of lysergic acid diethylamide (LSD) analogues (AL‐LAD, 1P‐LSD, and ETH‐LAD) and the characteristics of those who use them. Methods: An anonymous self‐selected online survey of people who use drugs (Global Drug Survey 2016; N  = 96, 894), which measured perceived drug effects of LSD and its analogues. Results: Most LSD analogue users (91%) had also tried LSD. The proportion of U.K. and U.S. respondents reporting LSD analogue use in the last 12 months was higher than for LSD only. LSD analogue users described the effects as psychedelic (93%), over half (55%) obtained it online, and almost all (99%) reported an oral route of administration. The modal duration (8 hr) and time to peak (2 hr) of LSD analogues were not significantly different from LSD. Ratings for pleasurable high, strength of effect, comedown, urge to use more drugs, value for money, and risk of harm following use were significantly lower for LSD analogues compared with LSD. Conclusions: LSD analogues were reported as similar in time to peak and duration as LSD but weaker in strength, pleasurable high, and comedown. Future studies should seek to replicate these findings with chemical confirmation and dose measurement.